Static balancing and power consumption for industrial robots and process machines for various purposes. Issue 1 (February 2021) - Matsko, O N; Volkov, N A; Kornilova, A A; Podkolzina, L V
Abstract: The paper presents the results of research and evaluation of the effectiveness of static balancing of cyclic drives of industrial robots and process equipment in order to reduce the instantaneous power consumption. Efficiency depends on the law of motion and its parameters, as well as the machine dynamics. The power consumption to overcome the counterweight inertia may exceed the power consumption to overcome unbalanced vertically moving parts. Mathematical models that quantitatively link the inertia characteristics of a machine, the law of motion, and instantaneous power are developed and studied, being the basis of the design methodology for modern high-performance machines.